Guatemala : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key findings of the Fiscal Transparency Evaluation report on Guatemala. Guatemala has transparency practices that achieve the ratings of basic, good, and advanced regarding three-quarters of the principles established in the IMF's Fiscal Transparency Code. The wealth of information available and the systems in place related to the public sector's execution of its budget, finances, and accounts allow for easy access by the population to an impressive volume of fiscal data. However, there is much room for improvement in the area of fiscal transparency. Establishing a new fiscal pact in which the medium-term fiscal targets are defined would help create fiscal predictability and ensure that the major challenges of social and economic development are met.